Pode ser a Gota D água: em cena a tragédia brasileira da década de 1970 - Sousa, Dolores Puga Alves de (2009)
The investigation aims to build a dialogue between art and society, from the reflection of the dramatic texts Medea of Euripides (431 BC), Medea Oduvaldo of Vianna Filho (1972), and Gota D água by Chico Buarque and Paulo Pontes (from 1975), including how the idea of tragedy is redraw with the movement of two different historical periods: the ancient Greece and Brazil in the 1970 s. These are two of the Brazilian reappropriate tragic piece of Euripides, in order to build a critical reasoning about the economic miracle of the military dictatorship, its authoritarianism, and the dynamics of a capitalist system that required more social inequality. The written works were analyzed, along the verses and songs from Gota D água main subject of this work. The musical theater of the brazilian s dictatorship period was taken into account for the approach of the play, beyond the development of her show the years 1975 to 1977 by director Gianni Ratto, in Rio de Janeiro and São Paulo. Understood the career of the authors, Vianinha and Ratto to find their esthetic and political ideas during this historic moment. To investigate the production, the program part of the show and the photos were relevant points in the research. Similarly, an examination was necessary on the categorical assessment that the critics had of Gota D água, indicating their views about a theater actually engaged for the period, holding a position that the staging of the play was what they called commercial ; big theater , and therefore only business, as was done in large rooms for shows. In the historiography of brazilian s theater, even with success in public, this work has been characterized as replication of the speech of the government s power for many intellectuals.